Determination of Hydroquinone in Whitening Cream Cosmetics in the Industrial Area of East Serang using UV-VIS Spectrophotometry Method - Rusdiana, Nita; Zenith Putri Dewiyanti; Heriyana Heriyana (Universitas Muhammadiyah Yogyakarta, 2026)
Hydroquinone is an active compound used to reduce reversible skin hyperpigmentation. This is why hydroquinone is often used as a bleach in creams. In this study, qualitative and quantitative analyses of hydroquinone in whitening cream cosmetic products circulating in the East Serang Industrial Estate, Serang Regency, which do not have an Indonesian Food and Drug Authority (BPOM) registration number, were performed. The sample in this study consisted of eight purposively selected samples, coded A, B, C, D, E, F, G, and H. The qualitative test was performed by determining the reagent's color with a FeCl3 solution. A quantitative test was carried out by determining the levels of hydroquinone compounds using a UV-Vis spectrophotometric method. The color reagent test results showed that all eight cream samples were positive for hydroquinone. The results of the quantitative test revealed that the eight positive cream samples contained hydroquinone with a sample A content of 2.10%, B by 1.70%, C by 4.34%, D by 5.61%, E by 6.11%, F by 1.77%, G by 5.40%, and H by 8.33%. Overall levels of hydroquinone in the samples used in this study exceeded the limit set by the Indonesian Food and Drug Authority (BPOM), which should not exceed 0.00%.